Psychometric validation of the PERMA-profiler as a well-being measure for student veterans. Issue 3 (2nd April 2020) - Umucu, Emre; Wu, Jia-Rung; Sanchez, Jennifer; Brooks, Jessica M.; Chiu, Chung-Yi; Tu, Wei-Mo; Chan, Fong
Abstract: Objective: The current study aims to validate the PERMA-Profiler, a well-known well-being measure, among a sample of student veterans. Participants: A sample of 205 student veterans were recruited from universities across the United States. Method: Cross-sectional research design was used in this study. Measurement structure of the PERMA-Profiler was evaluated using exploratory factor analysis (EFA). Convergent, divergent, and criterion-related validity was tested using Pearson correlation coefficients and Kruskal-Wallis test. Results: The EFA results yielded a two-factor solution for student veterans. Factors are named as emotional character strengths and performance character strengths. Conclusions: The PERMA-Profiler is a multidimensional scale with good reliability and acceptable levels of convergent, divergent, and criterion-related validity. The PERMA-Profiler can help researchers and practitioners better gauge well-being in student veterans. Implications will be discussed.